Scalar Field Dark Matter Around Charged Black Holes - Cruz-Marin, N; Gomez-Diaz, L (American Physical Society, 2024)
In this paper, we investigate the behavior of a massive scalar field dark matter scenarios in the large mass limit around a central Reissner-Nordström black hole. This study is motivated by observations from the Event Horizon Telescope collaboration, which does not exclude the possibility of the existence of such black holes. Through these inquiries, we uncover that the electric charge may significantly impact the scalar field profile and the density profile in the vicinity of the black hole. For the maximum electric charge allowed by the constraints of the Event Horizon Telescope, the maximum accretion rate decreases by ∼50% compared to the Schwarszchild case for marginally bound orbits. The maximum accretion rate of the massive scalar field is approximately ṀSFDM∼10-8M⊙ yr-1, which is significantly lower than the typical baryonic accretion rate commonly found in the literature. This implies that the scalar cloud located at the center of galaxies may have survived until present times. © 2024 American Physical Society.